PEMBERDAYAAN ORANG TUA MELALUI EDUKASI PARENTING ISLAMI BERBASIS VIDEO HOME EDUCATION UNTUK MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK DI DESA - Sutrisni Sutrisni; Uswatun Hasanah Usnur; Laila Darma Sari; Ridha Sakinah; Elvida Hanum (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
Early childhood cognitive development is a fundamental aspect that is greatly influenced by parenting styles and parental involvement at home. However, parents in Perbahingan Village face challenges such as limited knowledge regarding parenting strategies that align with Islamic values ​​and children's needs, as well as a lack of practical educational media. This Community Service (PKM) program aims to empower parents through Islamic parenting education based on home education videos. Implementation methods include problem identification, developing materials based on the Quran and Hadith, creating and distributing educational videos, conducting outreach, participating in mentoring, and evaluating. The results of the activity showed a significant increase in parents' understanding of Islamic parenting concepts and the crucial role of families in cognitive stimulation. Parents transformed into more active providers of stimulation through educational and positive daily activities. The use of home education videos has proven highly effective due to their flexibility, accessibility, and the ability to be replayed as needed by parents in rural areas. The tangible impact is seen in improving children's thinking, communication, and simple problem-solving skills. Thus, this digital-based empowerment model is an innovative and applicable strategy to optimize early childhood development while simultaneously strengthening the quality of family education in a sustainable manner in areas with similar problems. ABSTRAK Perkembangan kognitif anak usia dini merupakan aspek fundamental yang sangat dipengaruhi oleh pola asuh dan keterlibatan orang tua di rumah. Namun, orang tua di Desa Perbahingan menghadapi kendala keterbatasan pengetahuan mengenai strategi pengasuhan yang selaras dengan nilai Islam dan kebutuhan anak, serta minimnya media edukatif yang praktis. Pengabdian kepada Masyarakat (PKM) ini bertujuan memberdayakan orang tua melalui edukasi parenting Islami berbasis video home education. Metode pelaksanaan meliputi identifikasi masalah, penyusunan materi berlandaskan Al-Qur’an dan Hadis, pembuatan serta distribusi video edukasi, sosialisasi, pendampingan partisipatif, hingga evaluasi. Hasil kegiatan menunjukkan peningkatan signifikan pada pemahaman orang tua mengenai konsep parenting Islami dan peran krusial keluarga dalam stimulasi kognitif. Orang tua bertransformasi menjadi lebih aktif dalam memberikan stimulus melalui kegiatan harian yang edukatif dan positif. Penggunaan media video home education terbukti sangat efektif karena sifatnya yang fleksibel, mudah diakses, dan dapat diputar ulang sesuai kebutuhan orang tua di pedesaan. Dampak nyata terlihat pada peningkatan kemampuan berpikir, berkomunikasi, serta pemecahan masalah sederhana pada anak. Dengan demikian, model pemberdayaan berbasis digital ini merupakan strategi inovatif yang aplikatif untuk mengoptimalkan perkembangan anak usia dini sekaligus memperkuat kualitas pendidikan keluarga secara berkelanjutan di wilayah dengan permasalahan serupa.